Waiting zones and black holes: An analysis of the airport setting in Sérgio Tréfaut's Journey to Portugal. Issue 2 (1st October 2017) - Prata, Ana Filipa
This article aims to discuss the representation of the airport as a waiting zone in the film Viagem a Portugal (Journey to Portugal) (2011) by Sérgio Tréfaut in which, within a minimal poetical and rhetorical composition overexposed and dramatized in fiction, are depicted the hidden procedures of borderland security and immigration policing. Combining an oppressive accumulation of spatial, temporal and communicational elements, this standstill territory is characterized simultaneously as a black hole from where one cannot escape and a threshold of segregation and prejudice where difference is produced. This article analyses how in this movie the airport assumes the form of a 'banopticon' where suspicious individuals are prevented from entering, interrogated and forced to return to their origin countries, in order to stress the different rhythms of waiting in contemporary contexts of travel and mobility.